Words speak louder than pictures for action concepts: an eyetracking investigation of the picture superiority effect in semantic categorisation. Issue 9 (20th October 2016) - Hung, Jinyi; Edmonds, Lisa A.; Reilly, Jamie
ABSTRACT: An evolving consensus holds that actions and objects are supported by at least partially distinct neurocognitive substrates. In addition, representational modality (e.g. pictures vs. words) moderates the speed and accuracy of semantic access for both word classes. The picture superiority effect refers to the advantage that pictures manifest relative to words across a range of object recognition and memory recall tasks. While the effect has been investigated exclusively in the context of static objects, it is unclear whether this modality advantage extends to the processing of actions and/or verbs. We report two eyetracking experiments examining the dynamics of modality-specific access to actions via associative semantic judgement tasks for actions depicted as pictures or words. A range of eyetracking and behavioural measures revealed that participants consistently showed a reversal of the picture superiority effect for action semantic categorisation. These results challenge the privileged access hypothesis and demonstrate further distinctiveness of the action-object processing dichotomy. We discuss implications for action semantic processing.